New Results for Some Generalizations of Starlike and Convex Functions. (25th September 2020) - Ebadian, Ali; Hameed Mohammed, Nafya; Analouei Adegani, Ebrahim; Bulboacă, Teodor
Abstract : The purpose of the current paper is to investigate several various problems for the categories S T L s, S N e ∗, and other related categories such as various new outcomes for the coefficients of f, together with majorization issues, the Hankel determinant, and the logarithmic coefficients with sharp inequalities and differential subordination implications.